Periconia citlaltepetlensis sp. nov. (Periconiaceae, Pleosporales): a psychrotolerant fungus from high elevation volcanic glacier (Mexico) - Calvillo-Medina, Rosa P.; Cobos-Villagrán, Aurora; Raymundo, Tania (Phytotaxa, 2020)
Periconia citlaltepetlensis sp. nov. is the first record of a fungus identified to species level from high elevation volcanic glacier in Mexico. It is a novel dothideomycete species supported by morphological, cultural characters and phylogenetic analysis (nucleotide sequences data rDNA analysis). The new species is characterized by conidiophores often with 2–4 enteroblastic, percurrent proliferations, large, globose, golden brown or reddish brown conidia that are borne singly or in basipetal chains, verrucose to irregular lobate crests, born singly or in basipetal chains of two conidia; acropetally proliferating; conidiogenesis holoblastic. The morphology of P. citlaltepetlensis is compared to other Periconia species and a detailed description and morphological illustrations are provided.